AKT‐dependent sugar addiction by benzyl isothiocyanate in breast cancer cells. Issue 6 (5th March 2019) - Roy, Ruchi; Hahm, Eun‐Ryeong; White, Alexander G.; Anderson, Carolyn J.; Singh, Shivendra V.
Abstract : The overall promise of breast cancer chemoprevention is exemplified by clinical success of selective estrogen receptor modulators and aromatase inhibitors. Despite clinical efficacy, these interventions have limitations, including rare but serious side effects and lack of activity against estrogen receptor‐negative breast cancers. We have shown previously that dietary administration of benzyl isothiocyanate (BITC), which occurs naturally as a thioglucoside conjugate in edible cruciferous vegetables, inhibits development of estrogen receptor‐negative breast cancer in mouse mammary tumor virus‐ neu (MMTV‐ neu ) transgenic mice. This study demonstrates AKT‐mediated sugar addiction in breast cancer chemoprevention by BITC. BITC‐treated MMTV‐ neu mice exhibited increased 2‐deoxy‐2‐( 18 F)‐fluoro‐D‐glucose ( 18 F‐FDG) uptake in mammary tumors in vivo in comparison with mice fed basal diet. Cellular studies using MDA‐MB‐231 and SUM159 human breast cancer cell lines revealed BITC‐mediated induction and punctate localization of glucose transporter GLUT‐1, which was accompanied by an increase in intracellular pyruvate levels. BITC treatment resulted in increased S 473 phosphorylation (activation) of AKT in cells in vitro as well as in mammary tumors of MMTV‐ neu mice in vivo. Increased glucose uptake, punctate pattern of GLUT‐1 localization, and intracellular pyruvate levels resulting from BITC exposure were significantly attenuated in the presence of a pharmacological inhibitor of AKT (MK‐2206). Inhibition of AKT augmented BITC‐mediated inhibition of cell migration and colony formation. BITC‐induced apoptotic cell death was also increased by pharmacological inhibition of AKT. These results indicate increased glucose uptake/metabolism by BITC treatment in breast cancer cells suggesting that breast cancer chemoprevention by BITC may be augmented by pharmacological inhibition of AKT.